Literature Review : Pencegahan Anemia Selama Kehamilan - Solehati, Tetti; Solihah, Amalia Rizqi; Ulfah, Diana; Rahmawati, Syoifa; Marlinda, Yani; Kosasih, Cecep Eli (Universitas Tribhuwana Tunggadewi, 2023)
Anemia is a significant concern during pregnancy, requiring proper treatment to prevent ongoing issues. This study aims to explore interventions for preventing anemia in pregnant women. Using databases like Ebsco, Pubmed, Proquest, and ScienceDirect with keywords 'intervention,' 'prevention of anemia,' and 'pregnancy,' articles meeting inclusion criteria—focusing on anemia prevention interventions, RCT/Quasi experiment research designs, full text, and publication between 2011–2020—were sought. Initially, 1,052 articles were retrieved, and after screening and validity assessment, the study considered the last 7 eligible articles. The findings addressed four main intervention themes: new iron supplements, nutritional provision, handbook utilization, and health promotion for pregnant women. This research sheds light on various interventions available for preventing anemia during pregnancy.